Rewilding landscapes with apex predators: cheetah (Acinonyx jubatus) movements reveal the importance of environmental and individual contexts - Dimbleby, James; Cristescu, Bogdan; Bandyopadhyay, Kathan; Rooney, Nicola Jane; Marker, Laurie (Frontiers in Conservation Science, 2024)
Rewilding landscapes through species or population restoration is an increasingly applied practice in biological conservation. There is expanding interest in wildlife release projects for apex predator population augmentation or reintroductions in historical ranges. Cheetahs (Acinonyx jubatus) are an IUCN Vulnerable-listed species with a declining global population facing major threats, which in southern Africa primarily include lethal persecution on livestock farms and bush encroachment transforming open habitats to woody areas. We used GPS radiocollars to monitor ten adult cheetahs from 2007 -2018 in the Central Plateau of Namibia encompassing an area restored as an open savanna field (13.7 km 2 ) located in a matrix of woodland savanna affected by bush encroachment. We generated a set of a priori hypotheses that tested the effects of various factors on cheetah movements indexed by step length. We compared cheetah movement metrics based on their history as wild, rehabilitated, and/or translocated individuals. Day/night activity, habitat type, and habitat edges were significant predictors of cheetah movement. Wild resident cheetahs displayed significantly longer steps than the other cheetah classes, possibly suggesting increased territorial behaviour in response to the presence of introduced cheetahs. Some cheetahs temporally segregated by moving extensively during daytime, but most individuals were primarily active during crepuscular periods. Small prey remained constant across time, whereas large prey declined over the study period. Cheetahs appeared to adjust behaviourally by increasing movements in years when large prey were scarce. Cheetahs appeared to be ecologically adaptable and behaviourally flexible in response to varying prey populations and when translocated to new environments, specifically at the interface between bush-encroached woodland and open savanna. Environmental settings and animal history need to be carefully considered in rewilding and ecosystem restoration, and monitoring of released and resident individuals, if present, is important to understand ecological dynamics at release sites.